Psychological Impact of Alopecia (Hair Loss/Baldness)- Hair Care Management (Homoeopathy for All, 2024)
Hair is almost like a social status  for both men and women, and also  children. Hair loss can affect scalp or  entire body. Anyone like men, women  and children can experience hair loss.  Baldness typically refers to excessive  hair loss from scalp. Hereditary hair  loss with age is the most common  cause of baldness. Some people prefer  to let their baldness run its course  untreated and unhidden. It can be the  result of heredity, hormonal changes,  medical conditions or medications.  Homoeopathy is considered as one  of the very best alternative system for  treating hair loss.
Keywords: Hereditary hair; roundish